NATURAL RADIATION SOURCES AND TRAGIC CONSEQUENCES OF RADIATION, EARTH RADIATION, TEACHING A PRACTICAL LESSON ON THE TOPIC OF RADIOBIOLOGICAL PROCESSES USING THE "CLUSTER" METHOD (American Journal of Pedagogical and Educational Research, 2023)
This method provides students of Samarkand State Medical University with the article "TAbiy RadiationNg Resources. Earth radiation. Teaching the subject "Radiobiological Processes" in pedagogical technologies "class" mode is a topic of free thinking, open thinking, thinking and radioactive radiation and nuclear the formation of knowledge and skills to freely explain personal thoughts about explosions will help create a sharoit. To conduct this practical lesson, students of the second year of the Faculty of Medical Biology of SamSTU were allocated two hours [1].